Representation of a minority community in a Malaysian Tamil Daily - Ponmalar, N. Alagappar; David, Maya Khemlani; Ramayan, Sri Kumar (M. S. Thirumalai, 2009)
The media plays an important role in shaping attitudes of people but, at the same time, the media represents what occurs at ground level. This study examines the coverage of news stories in one Malaysian Tamil daily i.e., Malaysian Namban in August 2007, October 2007 and November 2007. This period encompasses the period just before and during the first month of the Hindu Rights Action Force (Hindraf) movement. Hindraf is a fairly new coalition of 30 Hindu Non-Governmental organizations committed to the preservation of Hindu community rights and heritage in multiracial Malaysia. The Tamils comprise 90% of the Malaysian Indian population and members of Hindraf are mainly Tamils. The Malaysian Indian population makes up 7% of the total population of the country and is considered a minority in the country. With a view to determining how the Malaysian Indian community, mainly the Tamils, are perceived by the media in multilingual and multiracial Malaysia, a content analysis of one Tamil daily was conducted to determine the type of news stories reported during this period.